INSKRIPSI HURUF ARAB DAN RAGAM HIAS PADA MASJID TUA AL-MUJAHIDIN KABUPATEN BONE SULAWESI SELATAN - Muslihin Sultan (Balai Penelitian dan Pengembangan Agama Makassar, 2012)
Archaeology is history; archaeological research cannot be separatedfrom the history, because historyreveals the story of material culture. The Old Mosque is part of a cultural thing that will describe thehistory of the Islamic society and the reconstruction of the mosque building in accordance with localcultural character of local genius in its time. The Old Mosque of al-Mujahidin Watampone is the oldestand the first mosque of the royal heritage of Bone in Islam development era. The mosque has specificstylistic and architecture that describes how the Islamic symbols interacted with local culture and art.The strong influence of Islamic teachings was implicitly reflected in a wide variety of the mosqueornaments. This research aims to reveal the decoration and Arabic inscriptions located in theOld Mosque, to promote the history and archaeological traces of the Islamic kingdom of Bone, and torecommend to the local government of Bone to make Qadi's cemetery as part of archeological historyof the kingdom Bone that deserve to be considered by the community and the Government of Bone as acultural heritage of the archipelago to be protected as Objects of Cultural guaranteed by IndonesianLaw Number 5 of 1992 about Objects of Cultural Property. The research methodology was a fieldresearch with a survey which is descriptive, archaeological, historical, and explanative on the OldMosque al-Mujahidin, Watampone, Bone regency, South Sulawesi. The techniques of collecting datain this study were: literature data, field data (archaeological assessment, observation, and interviews),documentation and recording, surface surveys, and the withdrawal of sampling. This study also usedthe architectural analysis on the mosque, i.e. morphological, technological, stylistic, and contextualanalysis.